2015
DOI: 10.3390/su7055321
|View full text |Cite
|
Sign up to set email alerts
|

A Generic Software Development Process Refined from Best Practices for Cloud Computing

Abstract: Cloud computing has emerged as more than just a piece of technology, it is rather a new IT paradigm. The philosophy behind cloud computing shares its view with green computing where computing environments and resources are not as subjects to own but as subjects of sustained use. However, converting currently used IT services to Software as a Service (SaaS) cloud computing environments introduces several new risks. To mitigate such risks, existing software development processes must undergo significant remodeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…(1) Abuse and nefarious use of cloud computing (2) Insecure application programming interfaces (3) Malicious insiders (4) Shared technology vulnerabilities (5) Data loss/leakage (6) Account, service and traffic hijacking (7) Unknown risk profile Extensive related studies on the security of cloud computing have been reported [27]. Several specific review works on the security are summarized in Table 2.…”
Section: Concept Of Cloud Computing Security Issuesmentioning
confidence: 99%
“…(1) Abuse and nefarious use of cloud computing (2) Insecure application programming interfaces (3) Malicious insiders (4) Shared technology vulnerabilities (5) Data loss/leakage (6) Account, service and traffic hijacking (7) Unknown risk profile Extensive related studies on the security of cloud computing have been reported [27]. Several specific review works on the security are summarized in Table 2.…”
Section: Concept Of Cloud Computing Security Issuesmentioning
confidence: 99%